Antiproliferative activities of methanolic extract of Chromolaena odorata (L.) R.M. king & H.Rob in a mice model - Rosli, Nor Fazirah (2019)
Chromolaena odorata and Melastoma malabathricum are plants that normally found in wasteland in Malaysia and both have great value in wound healing. Previous literatures reported that these plants possess antiproliferative, antibacterial and antiinflammatory effects. This study was conducted to investigate the antiproliferative activity of the methanolic extract of C.odorata (MeCO) in a mice model. The antiproliferative effect was conducted by MTT assay and the results revealed that MeCO has higher antiproliferative effect with IC50 value 78 μg/ml compared with M. malabathricum (no IC50 value). Thus, MeCO was chosen for in vivo experiment. For acute oral toxicity study, mice were divided into two groups, control and treatment (5000 mg/kg of MeCO). Results showed that there was no significant different of mice administered with MeCO in body weight. However, food intake of treatment mice was significant different (p < 0.05) compared to control group. There was significant decrease (p < 0.05) of lung weight in treatment group compared to control group. However, there was no significant difference in relative organ weight of liver, kidney and spleen of the treatment group compared to control group. Besides, the serum biochemical analysis showed that there was no significant different of mice administered with plant extract compared to control except alkaline phosphatase (ALP). ALP was significantly lower (p < 0.05) compared to control group. Histological examination showed normal architecture for spleen and kidney in both groups. However, mild congestion observed in liver and lungs of treatment group. For efficacy study, the mice were divided into six groups (n = 6) which were 250 mg/kg MeCO, 500 mg/kg MeCO, 1000 mg/kg MeCO, control (normal), untreated control mice and vehicle control. The mean survival time of the treatment groups was significantly higher (p < 0.05) compared to untreated control group. The liver weight of untreated control, 250 mg/kg and 500 mg/kg was significantly higher (p < 0.05) compared normal group. Besides, the tumour weight of mice treated with 1000 mg/kg was significantly lower (p < 0.05) compared to untreated control group. Serum biochemical analysis showed that the glucose was significantly different (p < 0.05) in all groups compared to the normal while urea level in vehicle control was significantly lower (p < 0.05) compared to normal. Histopathological examination resulted in metastasis of the mammary tumour to various organs such as spleen, liver, lungs in all groups. In conclusion, the MeCO extract has a potential of antiproliferative agent in breast cancer in vitro and in vivo.